Evaluation Of Iatf Protocols With Frozen Vs. Chilled Semen In Brahman Cattle - Porras Vargas, Jose Luis; Maldonado Castro, Gerardo Antonio; RODRIGUEZ MOLANO, CARLOS EDUARDO (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This research compared pregnancy percentages when using frozen semen and chilled semen in a seasonal mating program with fixed term artificial insemination (FTAI) in Brahman cattle. Semen was collected from a Brahman bull with confirmed fertility, identified sperm characteristics, and complete reproductive examination. A total of 140 Brahman cows were selected and divided into two groups of 70 cows each as follows: group 1 was inseminated with frozen semen and group 2 was inseminated with refrigerated semen. The frozen semen was collected by electroejaculation, evaluating its characteristics and conserving it in liquid nitrogen for 3 months until its use in the IATF program. The refrigerated semen was collected on the day of the IATF program, evaluating the characteristics of the semen, diluting it and refrigerating it until its use in the IATF. The pregnancy diagnosis was made 45 days post service by means of rectal palpation and ultrasonography, obtaining a pregnancy percentage of 41.42% with frozen semen and 60% with refrigerated semen. It was concluded that the refrigerated semen presented better semen characteristics and achieved the highest pregnancy rate.